Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1007/s00428-009-0791-1
|View full text |Cite
|
Sign up to set email alerts
|

LANA-1, Bcl-2, Mcl-1 and HIF-1α protein expression in HIV-associated Kaposi sarcoma

Abstract: Human herpesvirus 8 (HHV8) is necessary for Kaposi sarcoma (KS) to develop, but whether the tissue viral load is a marker of KS progression is still unclear. Little is known about the level of expression of apoptosis-regulating proteins and of hypoxia-inducible factors (HIFs) in KS tumour cells relative to HHV8 expression. We therefore investigated the expression of the latency-associated nuclear antigen (LANA-1) of HHV8, Bcl-2, Mcl-1, Bax, Bcl-xL, caspase 3 and HIF-1alphain KS tissue specimens at different st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 51 publications
1
19
0
3
Order By: Relevance
“…Early-stage KS represents a reactive lesion that can either regress or progress. Progression is related to the long-lasting expression of HHV8 latency genes in KS lesions, including latent nuclear antigen-1 (LANA-1),21 cyclin-D1,27,28 and bcl-2 29. HHV8-related induction of the receptor tyrosine kinase c-kit was shown by gene expression profiling in cultured endothelial cells to play a key role in KS tumorigenesis 30,31…”
Section: Hiv-associated Kaposi Sarcoma and Its Problems In Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Early-stage KS represents a reactive lesion that can either regress or progress. Progression is related to the long-lasting expression of HHV8 latency genes in KS lesions, including latent nuclear antigen-1 (LANA-1),21 cyclin-D1,27,28 and bcl-2 29. HHV8-related induction of the receptor tyrosine kinase c-kit was shown by gene expression profiling in cultured endothelial cells to play a key role in KS tumorigenesis 30,31…”
Section: Hiv-associated Kaposi Sarcoma and Its Problems In Diagnosismentioning
confidence: 99%
“…LANA-1 protein may cause dysfunction of cell cycle regulatory checkpoints by degrading p53 and inactivating pRb 37. It has been previously shown that positive immunostaining for HHV8 LANA-1 exhibits high sensitivity and specificity, and it is a reliable and cost-effective method for the diagnosis of KS and is also useful for distinguishing it from the mimickers 21,25,29…”
Section: Biomarkers Used In Hiv-ks Diagnosis/prognosismentioning
confidence: 99%
“…Furthermore, both latent antigens LANA and vIRF3 play a role on the HIF1 α stabilization via protein–protein interaction (Cai et al , 2006b, 2007; Shin et al , 2008). Recent analysis of clinical patient samples further supported a role for LANA in stabilization of HIF1α (Long et al , 2009). Interestingly, the lytic antigen vGPCR has also been shown to upregulate VEGF expression through activation of HIF1α expression (Sodhi et al , 2000).…”
Section: Kshv Primary Infectionmentioning
confidence: 98%
“…Ex vitro and animal experiments have shown that vitamin D can induce mouse myeloid leukemia cell differentiation and prolong the survival time of leukemia mice. Additional studies (Seo et al, 2005;Long et al, 2009) Recent studies have found that ATRA and vitamin D can significantly improve the sensitivity of multidrug resistance of tumor cells to chemotherapy drugs. Studies have also confirmed that ATRA and vitamin D, combined with chemotherapy, have a synergistic effect on the enhancement of lung cancer susceptibility.…”
Section: Discussionmentioning
confidence: 99%